1987
DOI: 10.1002/1097-0142(19870815)60:4<820::aid-cncr2820600418>3.0.co;2-y
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of N-myc amplification in relation to disease stage and histologic types in human neuroblastomas

Abstract: Both untreated and treated primary neuroblastomas from 52 patients were analyzed to determine the correlation between the amplification of N-myc oncogene and various prognostic factors. Amplification of N-myc was observed in eight of 28 untreated cases and in 12 of 24 treated cases. As a whole, 12 of 18 tumors (67%) in Stage IV had N-myc amplification, but there were fewer cases in the unadvanced disease stage, as reported previously by others. Furthermore, the authors detected N-myc amplification in three of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
0
1

Year Published

1990
1990
2008
2008

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(22 citation statements)
references
References 23 publications
3
18
0
1
Order By: Relevance
“…Twenty-two of 45 patients (49%) lacking p16 expression died within 5 years, whereas only two of 29 patients (7%) with p16 expression died within this period (Figure 4). Although age and N-myc ampli®cation have been known as signi®cant prognostic factors in neuroblastoma (Tsuda et al, 1987;Tonini, 1993), loss of p16 expression was not correlated with age and N-myc ampli®cation.…”
Section: Relationship Of Loss Of P16 Expression With Clinicopathologimentioning
confidence: 79%
“…Twenty-two of 45 patients (49%) lacking p16 expression died within 5 years, whereas only two of 29 patients (7%) with p16 expression died within this period (Figure 4). Although age and N-myc ampli®cation have been known as signi®cant prognostic factors in neuroblastoma (Tsuda et al, 1987;Tonini, 1993), loss of p16 expression was not correlated with age and N-myc ampli®cation.…”
Section: Relationship Of Loss Of P16 Expression With Clinicopathologimentioning
confidence: 79%
“…These original ®ndings have generally been con®rmed in subsequent studies (Combaret et al, 1996;Rubie et al, 1997;Tsuda et al, 1997). Overall, N-MYC ampli®cation remains the most widely accepted predictive parameter of long-term, disease-free survival.…”
Section: Neuroblastoma (Nbl)mentioning
confidence: 85%
“…Studies of over 800 patients with neuroblastoma (Bertram & Berthold, 1987;Nakagarawa et al, 1987;Tsuda et al, 1987, and see Brodeur, 1990 for review), a tumour of primitive neuronal cells which occurs predominantly outside the brain, have shown that amplification of the N-myc oncogene is associated with rapid progression and poor prognosis. Another oncogene which may serve as a marker of prognosis is c-erbB-2 (or HER-2 or neu).…”
Section: Discussionmentioning
confidence: 99%